Євроінтеграційні наміри українців крізь призму правового менталітету - Копельців-Левицька, Єлизавета Деонізіївна; Копельцив-Левицкая, Елизавета Деонизиевна; Kopel'civ-Levickaja, Elizaveta (Одеса : Юрид. л-ра, 2014)
In the article it is defined the influence of legal mentality on the process of formation of European integration tendency of Ukrainian foreign policy, it is also studied the legal system through the prism of legal mentality, it is proved the thought about belonging of legal mentality of Ukrainian peoples to western model.
Копельців-Левицька Є. Д. Євроінтеграційні наміри українців крізь призму правового менталітету / Є. Д. Копельців-Левицька // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 48-54.
Keywords: правова ментальність; правова система; євроінтеграція; правовая ментальность; правовая система; евроинтеграция; legal system; legal mentality; European integration